Mindful Self-Care as Predictor of Stress in Working and Non-working Married Women - Rida Nasir; Ayesha Akram; Syeda Afnan, (Dialogue Social Science Review (DSSR), 2025)
This research investigates the relationship between mindful self-care and stress levels in married women, comparing working and non-working groups. A cross-sectional design was employed, involving married women, and utilizing validated scales to assess mindful self-care components and stress levels. The results showed significant negative correlations between self-care dimensions and stress, indicating that higher levels of self-care are associated with lower stress levels. Notably, Self-Compassion and Purpose emerged as a strong protective factor. Contrary to expectations, the study found no significant difference in stress levels between working and non-working women, though working women reported slightly higher engagement in Mindful Relaxation and Physical Care. The findings suggest that mindful self-care plays a similar role in buffering stress for both working and non-working married women, highlighting its universal importance for their well-being. The study emphasizes the need for tailored interventions promoting holistic self-care practices to mitigate stress in this population. Keywords: Mindful Self-Care, Stress, Married Women, Mental Health